2008
DOI: 10.1111/j.1471-4159.2007.05030.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake and lysosomal delivery of galactocerebrosidase tagged with the HIV Tat protein transduction domain

Abstract: A number of studies have shown that a short peptide, the protein transduction domain (PTD) derived from the HIV‐1 Tat protein (Tat‐PTD) improved cellular uptake in vitro and distribution in vivo of recombinant proteins bearing such PTDs when administered systemically. To investigate the effects of Tat‐PTD addition on the subcellular localization of the lysosomal enzyme galactocerebrosidase (GALC, EC 3.2.2.46) and with a view towards designing improved therapeutic strategies for Krabbe disease (globoid cell leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Previously, Tat has been tested in mouse GALC. 20 Tat-fusion increased the secretion rate and M6P receptor–independent uptake of mouse GALC. Our study further confirmed these Tat effects in human GALC.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previously, Tat has been tested in mouse GALC. 20 Tat-fusion increased the secretion rate and M6P receptor–independent uptake of mouse GALC. Our study further confirmed these Tat effects in human GALC.…”
Section: Discussionmentioning
confidence: 90%
“…This was not seen in other lysosomal enzymes with Tat-fusion in previous studies. 17,20 We therefore studied the potential mechanism for the increased expression of GALC-Tat.…”
Section: Resultsmentioning
confidence: 99%
“…Research has reported that mimovirus vaccines with sizes similar to viruses can induce cellular immunity (Wu et al 2002, Yang et al 2008. Other studies also have indicated that mimovirus vaccines induce cellular and humoral immune responses (Zhang et al 2008). These studies demonstrate that mimovirus vaccines could be developed as an ideal contraceptive vaccine to induce immune responses and suppress fertility.…”
Section: Discussionmentioning
confidence: 99%
“…TAT has also been used for lysosomal delivery of PTs under the frame of ERT in some lysosomal disorders (159). Ohta's group (143) ligated the TAT domain to the super-antiapoptotic factor FNK to produce the PTD-FNK fusion protein.…”
Section: Organelle Targetingmentioning
confidence: 99%